Faktor Penyebab Ketidakteraturan Siklus Menstruasi Pada Remaja di SMAN 4 Tuban - Sari, Farah Hanis Dwi Kartika; P, Teresia Retna; Wahyurianto, Yasin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Reproductive health problems that are often experienced by women are menstrual disorders. The normal menstrual cycle lasts for 21-35 days, 2-8 days is when menstrual blood comes out which ranges from 20-60 ml per day. The results showed that 8 out of 10 female students who experienced irregular menstrual cycles were caused by academic stress. The aim is to describe the factors that cause irregular menstrual cycles in adolescents at SMA Negeri 4 Tuban. Descriptive research design with a cross-sectional approach. The study population was all young women at SMAN 4 Tuban, with a sample size of 87 teenagers. The sampling technique used is Total Sampling. The research variable is the factors that cause irregular menstrual cycles in adolescents. The method of collecting data was by distributing questionnaires. The results showed that almost half (46%) of adolescents experienced menstrual cycle irregularities, a small proportion (1%) of adolescents experienced severe stress and almost half (45%) of adolescents experienced moderate stress, almost half (28%) of adolescents had thin nutritional status and some small (9%) adolescents have obese nutritional status, all adolescents (100%) have poor eating habits, almost all (86%) adolescents have a sleep duration of less/more than 8 hours, and most (60%) adolescents do light activity and a small proportion (2%) do strenuous activity. The school should provide an appeal through banners/posters containing movements for a healthy lifestyle, normal sleep duration, regular exercise and maintaining a good diet.